Rigid polyurethane foams from lignin based polyols - Cateto, C.A. (2010)
Rigid polyurethane (RPU) foams were synthesized using lignin-based polyols obtained by an oxypropylation process. Alcell, Indulin AT, Curan 27-11P and Sarkanda lignins have been oxypropylated using formulations deduced from an optimization study with Alcell. L/PO/C (ratio between lignin, PO and catalyst content) of 30/70/2 and 20/80/5 were used to obtain the desired polyols. The resulting RPU foams were characterized in terms of density, mechanical properties, conductivity and morphology. All Sarkanda lignin based polyols and the 30/70/2 Curan 27-11P polyol were found inadequate for RPU formulations. Alcell and Indulin AT based polyols and the 20/80/5 Curan 27-11P polyol resulted in RPU foams with properties very similar to those obtained from conventional commercial polyols. RPU foams produced with the 30/70/2 Alcell and the 30/70/2 Indulin AT polyols exhibited improved properties compared with those from 20/80/5 based formulations.